THE COMMUNICATIVE FUNCTIONS OF ULAON POGU NI ALAMAN IN EXHUMATION (MANGONGKAL HOLI) A FUNERAL CEREMONY IN TOBA BATAK - OSTI ELISABETH SIMANJUNTAK; Lidiman Sahat Sinaga; Syamsul Bahri (State University of Medan, 2020)
This research focused on communicative functions used in Ulaon Pogu ni Alaman in Exhumation (Mangongkal Holi) at funeral ceremony in Toba Batak. This research was conducted by applying descriptive qualitative method. The data were collected from the transcript utterances of Ulaon Pogu ni Alaman at funeral ceremony in Toba Batak. The findings of the study show that there are 100 utterances which consist of six communicative functions which is referential, emotive, poetic, conative, phatic, and metalinguistic. The most dominant type of communicative functions used in Ulaon Pogu ni Alaman in Exhumation (Mangongkal Holi) at funeral ceremony in Toba Batak is referential function. It means that the communication used in Ulaon Pogu ni Alaman intended to establish the description and contextual information that happened on that day. Keywords: communicative functions; Batak Toba; funeral ceremony; Ulaon Pogu ni Alaman.